Penggunaan Aplikasi Berbasis Internet Dalam Pemantauan Status Gizi Anak Stunting Di Posyandu Desa Tabumela, Kabupaten Gorontalo - Fadel Bilondatu; Ainun Dwi Silfani S. Dukalang; Anugrah Haq (Madu Jurnal Ilmu Kebidanan, 2026)
Growth monitoring for stunted children at community health posts often faces practical barriers, including manual recording, delayed reporting, and inconsistent follow-up. Internet-based applications may help address these problems, but local evidence on their use in stunted children remains limited. This study aimed to assess the use of an Internet-based application for monitoring the nutritional status of stunted children at community health posts in Gorontalo Province. A mixed methods design with an explanatory sequential approach was used. The quantitative component used a quasi-experimental pre-post design with two groups of participants. Twenty stunted children from posyandu were assigned to an intervention group (n=10) receiving application-based monitoring and a control group (n=10) receiving conventional monitoring. The measurements were conducted in October-November 2025. The qualitative component involved five respondents through in-depth interviews. As a preliminary study, the findings indicate that application use was associated with a difference in HAZ change patterns between groups (delta HAZ: +0.100 vs −0.175; p=0.040; Cohen’s d=0.99). These findings are hypothesis-generating and require confirmation in larger randomized studies. Interviews indicated that the application was generally well accepted, although its use was still influenced by the condition of anthropometric equipment, cadres’ skills, internet costs, and follow-up from health services. All measurements and data entry were performed independently by cadres without researcher intervention, reflecting real-world use conditions; this also represents a limitation as there was no external validation of input accuracy.